Implementation of Lean Software Development on Yarn Production Sample Complaint Application - pohan, sry dhina; Rizqi, Muhammad; Darnis, Rahmi; Widiana, Siska Ayu (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
At PT. Asia Pacific Fibers Tbk., the growth of polyester production industries is anticipated to enable the production of high-quality fiber in response to client demand. One of the divisions in charge of reviewing client complaints about thread sample issues is client Technical Service. In order to analyze the sample complaints, a lengthy procedure of reviewing the history of consumer purchases of yarn samples in a summary of the customer complaint list book was undertaken. In order to handle the process of processing customer complaints regarding thread samples by implementing the Laravel Framework, an application is required. The Laravel framework is an open source platform that aids in the speedy, reliable, and simple development of applications. Lean Software Development (LSD), which is based on the Agile Development model, is complicated in how Laravel handles coding on the Hypertext Preprocessor. the process that includes phases for needs analysis, design, system implementation, and testing. Blackbox is used to test application functionalities before User approval Testing (UAT) is done to gauge user approval of new apps. The Laravel Framework's UAT test results, which were attained by 85% in the building of consumer thread example complaint applications, can assist businesses in managing customer complaint data and adhering to business requirements.